Using an Electrochemical Aptasensor to Early Detect Prostate Specific and Free Prostate Specific Antigens Released by Cancer Cells - Parra, João P. R. L. L. [UNESP]; Crulhas, Bruno P. [UNESP]; Basso, Caroline R. [UNESP]; Delella, Flávia K. [UNESP]; Castro, Gustavo R. [UNESP]; Pedrosa, Valber A. [UNESP] (Wiley, 2018)
The detection of prostate cancer (PCa) in its early stage is essential to prevent metastasis. Patients who start their treatment earlier have greater chances to be cured; therefore, several research groups have been developing a simple and non-invasive methodology to detect PCa. The aim of this article is to report a new method to detect prostate specific (PSA) and free prostate-specific antigens (PSA) released by cancer cells based on the use of an aptasensor. Scanning electron microscopy (SEM), EDS and cyclic voltammetry were the instruments adopted to assess the surface of the biosensor. According to our results, the aptasensor was highly sensitive and recorded linear response 1–100 ng/ml of PSA and fPSA and detection limit 1.1 ng/ml. Studies on interfering compounds such as human serum protein, ascorbic acid, uric acid and mucin type I have shown low correlation to the used aptamer. Thus, this biosensor could be adopted in the near future to early diagnose PCa.
Keywords: Aptamer; Biosensor; fPSA; Prostate Cancer; PSA